Fire resistance of cold-formed steel framed shear walls under various fire scenarios - Andres, Blanca (Fire Mater, 2019)
This paper presents results of large-scale experiments with varying levels of fire severity on lateral force-resisting systems commonly used in cold-formed steel framed buildings. Gypsum-sheet steel composite panel sheathed walls, oriented strand board sheathed walls, and steel strap-braced walls are examined. Postflashover fire conditions of two different intensities as well as 1 hour of fire exposure similar to that in a standard furnace qualification test are studied. Additionally, a full-scale furnished kitchen fire experiment is conducted for comparison. The results highlight differences in the thermal response and subsequent performance of the walls as well as differing sensitives of the walls to pre-damage, eg, that might occur during an earthquake. The results are part of a larger effort to provide fragilities for these wall systems in response to realistic fires for performance-based design.